Oral Phenotype and Salivary Microbiome of Individuals With Papillon–Lefèvre Syndrome - Lettieri, Giulia Melo; Santiago, Luander Medrado; Lettieri, Giancarlo Crosara; Borges, Luiz Gustavo dos Anjos; Marconatto, Letícia; de Oliveira, Laudimar Alves; Damé-Teixeira, Nailê; Salles, Loise Pedrosa (Frontiers in Cellular and Infection Microbiology, 2021)
Papillon-Lefèvre syndrome (PLS) is an autosomal recessive rare disease, which main characteristics include palmoplantar hyperkeratosis and premature edentulism due to advanced periodontitis (formerly aggressive periodontitis). This study aimed to characterize the oral phenotype, including salivary parameters, and the salivary microbiome of three PLS sisters, comparatively. Two sisters were toothless (PLSTL1 and PLSTL2), and one sister had most of the teeth in the oral cavity (PLST). Total DNA was extracted from the unstimulated saliva, and the amplicon sequencing of the 16S rRNA gene fragment was performed in an Ion PGM platform. The amplicon sequence variants (ASVs) were obtained using the DADA2 pipeline, and the taxonomy was assigned using the SILVA v.132. The main phenotypic characteristics of PLS were bone loss and premature loss of primary and permanent dentition. The PLST sister presented advanced periodontitis with gingival bleeding and suppuration, corresponding to the advanced periodontitis as a manifestation of systemic disease, stage IV, grade C. All three PLS sisters presented hyposalivation as a possible secondary outcome of the syndrome. Interestingly, PLST salivary microbiota was dominated by the uncultured bacteria Bacterioidales (F0058), Fusobacterium, Treponema, and Sulfophobococcus (Archaea domain). Streptococcus, Haemophilus, and Caldivirga (Archaea) dominated the microbiome of the PLSTL1 sister, while the PLSTL2 had higher abundances of Lactobacillus and Porphyromonas. This study was the first to show a high abundance of organisms belonging to the Archaea domain comprising a core microbiome in human saliva. In conclusion, PLST individual does have a microbiota different from that of the periodontitis’s aggressiveness previously recognized. Due to an ineffective cathepsin C, the impairment of neutrophils probably provided a favorable environment for the PLS microbiome. The interactions of Bacteroidales F0058, Caldivirga, and Sulfophobococcus with the microbial consortium of PLS deserves future investigation. Traditional periodontal therapy is not efficient in PLS patients. Unraveling the PLS microbiome is essential in searching for appropriate treatment and avoiding early tooth loss.